Geographic and taxonomic variation in Batrachochytrium dendrobatidis infection and transmission within a highly endemic amphibian community. Issue 9 (3rd May 2013) - Bielby, J.; Bovero, S.; Angelini, C.; Favelli, M.; Gazzaniga, E.; Perkins, M.; Sotgiu, G.; Tessa, G.; Garner, T. W. J.; Green, David
Abstract Aim In a highly endemic, threatened amphibian assemblage, we measure and describe the geographic and taxonomic distribution of the amphibian chytrid fungus, Batrachochytrium dendrobatidis (Bd), with a view to identifying those sites and species most at risk of infection and its negative consequences. Additionally, we aimed to determine the potential for direct transmission events between two known carriers of Bd infection. Location The island of Sardinia. Methods We collected swab and tissue samples of amphibians from a wide range of geographic sites and species. We used epidemiological and statistical techniques to quantify deviations from a random distribution. We used random forests to investigate habitat use and overlap in two species known to be infected by Bd to quantify a surrogate measure of the contact rates between these two species. Results Both geographic and taxonomic distributions of Bd were highly non‐random: we identified a cluster of infections in the north of the island and found that two species, Euproctus platycephalus and Discoglossus sardus, had a relatively high prevalence of infection within this cluster. Our analyses suggest that, on the basis of their fine‐scale habitat use, they have relatively little opportunity for direct transmission and could maintain Bd infection independently. Main conclusions Our results illustrate how obtaining detailed information on the geographic and taxonomic distribution of infection is a useful first step in assessing the risk of infection for species within the region. Attempting to quantify possible routes of transmission amongst species further aids us in identifying mechanisms of pathogen persistence within the host community. Within this assemblage, we have identified two hosts that carry infection and may be at risk. Further, our research suggests that these two species may be able to maintain infection independently of one another, which has implications for attempts to mitigate this parasite.